2017
DOI: 10.1080/00918369.2017.1400314
|View full text |Cite
|
Sign up to set email alerts
|

Same-Sex Parenting: Identification of Social Representations in a Sample of Portuguese Professionals

Abstract: Although international scientific research and the position of professional associations reiterate that the parents' sexual orientation is not a criterion of parenting quality, the social recognition of same-sex parenting remains difficult in Portugal. Given the importance of forensic issues in this field, this study aims to identify the representations of psychologists, social workers, lawyers/attorneys, and judges regarding same-sex parenting. The study involves five homogeneous focus groups with a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…Although not considered in Lawson's original framework of intent to parent, there are reasons to believe that anticipated stigma may affect decision making (Hicks, 2000;Gartrell et al, 2005;Matthews and Cramer, 2006;Bos and van Balen, 2008;Eady et al, 2009;Yager et al, 2010;Mellish et al, 2013;Riskind et al, 2013;Bauermeister, 2014;FRA, 2014;Kimberly and Moore, 2015;Fontaine, 2016, 2017;Gato et al, , 2019Xavier et al, 2017;Eurobarometer, 2019;Scandurra et al, 2019;Tasker and Bellamy, 2019). In this regard, using a general measure of anticipated stigma upon parenthood (i.e., eliciting unfavorable reactions from others as a parent), Gato et al (2019) found that lesbian women considered themselves at a higher risk of becoming a victim of social stigma as a mother than did either bisexual or heterosexual women in Portugal.…”
Section: Anticipation Of Stigma Upon Parenthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Although not considered in Lawson's original framework of intent to parent, there are reasons to believe that anticipated stigma may affect decision making (Hicks, 2000;Gartrell et al, 2005;Matthews and Cramer, 2006;Bos and van Balen, 2008;Eady et al, 2009;Yager et al, 2010;Mellish et al, 2013;Riskind et al, 2013;Bauermeister, 2014;FRA, 2014;Kimberly and Moore, 2015;Fontaine, 2016, 2017;Gato et al, , 2019Xavier et al, 2017;Eurobarometer, 2019;Scandurra et al, 2019;Tasker and Bellamy, 2019). In this regard, using a general measure of anticipated stigma upon parenthood (i.e., eliciting unfavorable reactions from others as a parent), Gato et al (2019) found that lesbian women considered themselves at a higher risk of becoming a victim of social stigma as a mother than did either bisexual or heterosexual women in Portugal.…”
Section: Anticipation Of Stigma Upon Parenthoodmentioning
confidence: 99%
“…Research question 2: Which demographic and psychological factors are predictive of parenthood intentions, and is the nature or strength of these predictions associated with sexual orientation? H2: We expected anticipated stigma upon parenthood to mediate the relationship between sexual orientation and parenthood intentions, i.e., the effect of stigma will affect mostly LGB individuals' parenthood intentions (Hicks, 2000;Gartrell et al, 2005;Matthews and Cramer, 2006;Bos and van Balen, 2008;Eady et al, 2009;Yager et al, 2010;Mellish et al, 2013;Riskind et al, 2013;Bauermeister, 2014;FRA, 2014;Kimberly and Moore, 2015;Fontaine, 2016, 2017;Xavier et al, 2017;Eurobarometer, 2019;Scandurra et al, 2019;Tasker and Bellamy, 2019).…”
Section: Research Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…When investigating attitudes toward same-sex adoptive families among Portuguese students from helping professions, Fontaine (2016, 2017) found an association between modern heterosexism (subtler forms of prejudice) and negative attitudes toward adoptive parenting by lesbians and gay men. In turn, Xavier, Alberto, and Mendes (2017) identified social representations of same-sex parenting in the discourses of psychologists, social workers, lawyers, attorneys, and judges in Portugal with experience in the area of family and parenting. While some arguments asserted that sexual orientation did not define parenting quality, and some asserted specific competencies, many instances of expressed reservation about same-sex couples' access to parenthood were found (and these were particularly evident in the discourses of lawyers and attorneys).…”
Section: The Third Research Wave: Investigating the Unique Challenges Faced By Same-gender Couples Who Parent Togethermentioning
confidence: 99%
“…Devem ainda ser consideradas as oportunidades ou obstáculos ao nível legal, médico e social que, para além de determinarem a informação que se encontra ou não disponível, são preponderantes no acesso à parentalidade, podendo interferir nas intenções parentais (Aboim et al, 2012;Baiocco & Laghi, 2013;Berkowitz & Marsiglio, 2007;Bos et al, 2003;Brown et al, 2009;Chabot & Ames, 2004;Gianino, 2008;Goldberg, 2010;Rabun & Oswald, 2009;Touroni & Coyle, 2002). Por exemplo, um dos obstáculos pode advir das atitudes dos profissionais com quem lésbicas e gays terão que contactar nos serviços de adoção e saúde (e.g., Berkowitz & Marsiglio, 2007;Brown et al, 2009;Gianino, 2008;Xavier et al, 2017).…”
unclassified